Integrated Rural Development : science & technology, the road ahead - Indian Science Congress 2006 : Hyderabad, India); Rastogi, S. K.; National Institute of Science Communication and Information Resources (New Delhi, India) (New Delhi : National Institute of Science Communication and Information Resources, 2006)
Based on deliberations held by various sessions of the 93rd Indian Science Congress, held at Acharya N.G. Ranga Agricultural University, Hyderabad during January 3-7, 2006; includes interviews with leading scientists conducted by the team of NISCAIR scientists.
Includes index.
Keywords: Science -- India -- Congresses; Technology -- India -- Congresses; Rural development -- India -- Congresses